A Buffered Alcohol-Based Fixative for Histomorphologic and Molecular Applications. (July 2016) - Perry, Candice; Chung, Joon-Yong; Ylaya, Kris; Choi, Chel Hun; Simpson, Amari; Matsumoto, Kaipo T.; Smith, William A.; Hewitt, Stephen M.
Formalin-fixed paraffin-embedded (FFPE) tissue is the predominant preparation for diagnostic histopathological evaluation and increasingly the biospecimen on which molecular diagnostics are performed. However, formalin is carcinogenic and results in cross-linking of proteins and nicking and alterations of nucleic acids. Alternative fixatives, including 70% ethanol, improved biomolecular integrity; however, they have yet to replace neutral-buffered formalin (NBF). Herein, we describe the phosphate-buffered ethanol 70% (BE70) fixative. The histomorphology of BE70-fixed tissue is very similar to that of NBF; however, it is a non-cross-linking fixative and lacks the carcinogenic profile of formaldehyde-based fixatives. RNA isolated from tissue fixed in BE70 was of substantially higher quality and quantity than that was recovered from formalin-fixed tissue. Furthermore, the BE70 fixative showed excellent RNA and DNA integrity compared with that of NBF fixative based on real-time polymerase chain reaction analysis results. Immunohistochemical staining was similar for the antigen tested. In conclusion, BE70 is a non-cross-linking fixative that is superior to NBF and 70% ethanol with reference to biomolecule recovery and quality from paraffin-embedded tissue. Additional studies to compare the histomorphologic and immunohistochemical performance and utility in a clinical setting are required.